How to Capture Neighborhood Change in Small Cities - Kaida, Lisa; Ramos, Howard; Singh, Diana; McLay, Rachel (My University, 2020)
Small cities across North America are experiencing rapid changes, but methodological obstacles hamper researchers’ ability to analyze them. This research note explores some of the methodological challenges faced by researchers and offers solutions. Using Charlottetown, Prince Edward Island, as a case study, we show that a major challenge lies in choosing meaningful geographic units for small city neighborhoods, and we evaluate the benefits and drawbacks of several geographical options. Another major challenge is that the boundaries of existing units change between census years, demanding an approach to reconstructing them to allow for temporal analysis. We propose two feasible solutions for re-creating neighborhood geographic units over time: ‘moving forward’ and ‘going backward.’ Both involve selecting units from a particular census year to serve as a fixed point of reference for the re-creation of boundaries across multiple census years. We conclude by cautioning that studying changes in small cities over longer time periods in Canada is not feasible because of the extensive and complex boundary changes that have occurred between census years. We offer an approach for looking at shorter time periods.
Keywords: Neighborhood change; small cities; geographic unit; Dissemination Area; Aggregated Dissemination Areas; Census Tracts